Identification of TabZIP family members with possible roles in the response to auxin in wheat roots. (April 2022) - Tian, Xinyu; Jiang, Qinqin; Jia, Ziyao; Fang, Yan; Wang, Zhonghua; Wang, Jun
Abstract: Auxin regulates root development and is considered a potential target for improving crop yield. In this study, we identified 22 basic leucine zipper transcription factors (bZIP TFs) that responded to two concentrations (1 and 50 μM) of indole-acetic acid (IAA) during wheat root development by transcriptome analysis. In addition, we identified 176 TabZIP genes from the wheat genome. Phylogenetic classification and gene structure analysis indicated that the 22 auxin-responsive TabZIPs were divided into groups 1 to 9 (except group 3) with different functions. Phenotypic analysis showed that knocking out Arabidopsis AtHY5, which is the homologous gene of TabZIP6D_147 (one of the downregulated auxin-responsive TabZIPs under both 1 and 50 μM IAA that belonged to group 4), resulted in insensitivity to IAA, while the phenotype of TabZIP6D_147/hy5 complementary lines recovered to that of the wild type, suggesting that downregulated TabZIP6D_147 plays a negative role in the auxin signalling pathway. These results revealed that auxin-responsive TabZIP genes may play different roles in root architecture in the response to the two concentrations of auxin. Graphical abstract: Image 1 Highlights: Twenty-two auxin-responsive TabZIPs were identified by transcriptome analysis. The auxin-responsive TabZIPs played different roles under auxin treatments. One hundred seventy-six TabZIPs were identified from wheat genome. The downregulated TabZIP6D_147 negatively regulates root growth.